2016
DOI: 10.1586/14760584.2016.1124763
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus (HPV)-16/18 AS04-adjuvanted vaccine for the prevention of cervical cancer and HPV-related diseases

Abstract: Vaccines are available against human papillomavirus (HPV), the causal agent of cervical and other cancers. Efficacy data from the HPV-16/18 AS04-adjuvanted vaccine clinical trial program were reviewed. Six randomized, controlled phase II/III trials evaluating cervical endpoints enrolled women from diverse populations and geographical locations. The program analyzed extensively the cohorts most relevant from a public health perspective: the total vaccinated cohort (TVC), approximating a general population inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 80 publications
(153 reference statements)
1
27
0
Order By: Relevance
“…However, the impact of HPV infection on the prognosis of ESCC is still uncertain [ 2 , 35 ] . In addition, the recent advances in HPV vaccination can believed to improve the reduction of HPV-related tumors in non-gynecological cancers, which is a optimistic scenario to be proved in near future [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of HPV infection on the prognosis of ESCC is still uncertain [ 2 , 35 ] . In addition, the recent advances in HPV vaccination can believed to improve the reduction of HPV-related tumors in non-gynecological cancers, which is a optimistic scenario to be proved in near future [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar declines have been observed in Scotland and Denmark 4952 ( Table 1). There are randomised controlled phase 2/3 trials indicating that, despite diverse populations and geographical locations, HPV vaccines covering HPV16/18 provided some cross-protection against non-vaccine strain HPV and could protect women against cervical and non-cervical HPV-related infections 53 .…”
Section: Introductionmentioning
confidence: 99%
“…66 Potential role of vaccines Bivalent (HPV-16/18; Cervarix R ) and quadrivalent (HPV-6/11/16/18; Gardasil R ) vaccines target-ing the most common HPV types have been found to be effective in cervical, vulvar, oral, and anal cancer. 67 Studies investigating the efficacy of these two vaccines also observed cross-protection against some nonvaccine but oncogenic HPV types (e.g., HPV-31/33/45). More recently, nonavalent (HPV-6/11/16/18/31/33/45/52/58; Gardasil R ) vaccine has been approved in some countries.…”
Section: The Role Of Hpv Infection and Hpv Vaccines In Esophageal Squmentioning
confidence: 99%